Perspektif Pendidikan Ditinjau dari Batasan, Landasan Keilmuan dan Sistemnya - Zulyadaini Zulyadaini (Jurnal Ilmiah Universitas Batanghari Jambi, 2009)
Activity of eduction represent fair activiy of human and represent activity between generation. Its meaning in concerned in it (is) young and old generation in order to pushing young become society citizen. As everyday social reality hance activity of education represent concrete matter, and can perceive. Its of education can be interpreted 1) run activity or effort designedly, regular and berencana for the purpose of changing tune human being up at which is wanted’ 2). Consciousness to prepare edecative participant through activityof tuition, instruction and to practise to its role a period of the come 3). Effort and consciousness of terencana to realize atmosphere learn and study process so that educative participant actively develop x’self potency to have the power of religious spritual, selfcontrol, personality, intellegency, august behaviour os skiledfibre which needed by x’self, society, state and nation. There is four type of idea able to be made by the basis for education of mora, that is: 1). Idea about freedom of mind, what relate at action which pursuant to at confidence of someone 2). Idea about relate at behaviour integration and campatibility 3). Idea about benefection, where someone pay attention prosperity of others 4). Idea about justice, where someone be have fair with its group members 5). Idea about recompensation, what relate at penalization and hadia mathcing with certain behaviour. Band education : formal education, nonformal, and is informal. Education type include, cover education of public, vocational,. Akademik, profession, vokasi, religious and special. Education or study take place along the life (education lifelong, learning lifelong) and both : Education have four pillar or joint : 1). Knowing, including learning how learning (know to learning, learn to how learning including). 2) doing (do to learning) 3). Becoming someone (be to learning) and 4). Coexisting, life with other (livetogheter to learning) outhere wit live to learning).